Purchase Intention of Halal Products among Non-Muslim Consumers in Malaysia - Abdelwareth Hashem, Ebrahim Ali (2016)
The purpose of this research is to understand the purchase intention of Halal products among the Non-Muslim consumers in Malaysia, since there are limited studies and researchers have been conducted in regard to this area within the Malaysian context. The underlining theory for consumer purchase intention in this research is fundamentally the Theory of Planned Behaviour (TPB), which focuses on understanding how consumers’ purchase intention is influenced by certain factors. The factors that are involved in this research are the independent variables, which are Perception of Quality, Perception of Halal Logo Credibility, Consumer Attitude and Consumer Health Consciousness. The research methodology in this research uses the correlation design, which is a quantitative study to measure the relationship between the variables that are involved in this research. The sample size in this research is 202 participants and the research instrument tool used is self-administered questionnaire. However, the results of the correlation analysis are theoretically discussed and statistically analysed. The results found that there is a significant influence between Consumer Attitude and Consumer Health Consciousness towards the purchase intention of Halal products among the Non-Muslim consumers in Malaysia. While is there is no significant influence between Perception of Quality and Perception of Halal Logo Creditability towards the purchase intention of Halal products among the Non-Muslim consumers in Malaysia. Moreover, based on these results, recommendations “managerial implications” have been proposed, as they are believed to be useful for managers and marketers in the Halal industry in Malaysia to come up with strategies particularly communication strategies which can positively enhance the intention to purchase Halal products.